The Spirit in Colossians and Philemon: Love, Understanding, and Unity - Beers, Holly (Pneuma, 2021)
Abstract Though direct reference to the Spirit is relatively rare in Colossians and Philemon, the functions of the eschatological Spirit are in line with typical Pauline emphases. The Spirit is the one who enables both individuals and the community to love, to understand (and sing) so as to live in line with God’s purposes, and to be unified.